1979
DOI: 10.1161/01.res.45.6.764
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between changes in left ventricular bipolar electrograms and regional myocardial blood flow during acute coronary artery occlusion in the dog.

Abstract: The purpose of this study was to determine whether a quantitative relationship existed between a reduction in regional myocardial blood flow, measured by radiolabeled microspheres, and the degree and type of changes in myocardial activation recorded in bipolar left ventricular subepicardial and subendocardial electrograms, in open-chest dogs following acute coronary artery occlusion. We found that the degree of regional myocardial ischemia was related quantitatively to the reduction in amplitude recorded with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 34 publications
1
33
1
Order By: Relevance
“…Consistent with the study of Ruffy et al, 10 we observed no significant delay in subendocardial electrical activation during short-term ischemia. Therefore, electrical delay could not account for the observed dyssynchrony during ischemia.…”
Section: Relationship Between Regional Electrical and Mechanical Actisupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the study of Ruffy et al, 10 we observed no significant delay in subendocardial electrical activation during short-term ischemia. Therefore, electrical delay could not account for the observed dyssynchrony during ischemia.…”
Section: Relationship Between Regional Electrical and Mechanical Actisupporting
confidence: 93%
“…Possibly, more severe and longer lasting ischemia could induce conduction delays. 10,11 The aim of the present study, however, was to determine if onset AFG could identify mechanical activation in segments with decreased regional contraction, and we therefore used ischemia to depress myocardial function. Furthermore, the principle of onset AFG is such that it should identify delay in electrical activation regardless of etiology.…”
Section: Relationship Between Regional Electrical and Mechanical Actimentioning
confidence: 99%
“…This site spares the septum, so our mapping array covers and surrounds the risk zone (1). Ischemia was defined as a Ն45% decrease in bipolar electrogram voltage (1,2,28,36); all data in vivo or in vitro are reported as "ischemia" when this definition in vivo was met. We waited 60 min because infarct size in the open-chest dog is then ϳ75% of the risk zone (2).…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vivo studies have shown that, during AMI, endocardial (Endo) conduction remains comparatively preserved at a time when epicardial (Epi) conduction is delayed and fractionated [1][2][3][4][5]. Other studies have demonstrated that, despite similar changes in resting membrane potential, ischemia induces a greater depression of the action potentials of ventricular Epi vs Endo tissues [6,7].…”
Section: Introductionmentioning
confidence: 99%